A hot topic in hot times: how media coverage of climate change is affected by temperature abnormalities. (24th November 2020) - Pianta, Silvia; Sisco, Matthew R
Abstract: Media coverage of climate change is arguably a fundamental factor shaping climate change attitudes and possibly behaviors, but its trends and determinants are still underinvestigated. In this paper, we analyze a comprehensive dataset representing more than 1.7 million online news articles covering climate change in the 28 countries of the European Union in 22 different languages for the period 2014–2019. We combine our news dataset with observed temperature data to investigate whether and how temperature abnormalities influence media coverage of climate change. We find that the strongest determinants of media coverage are positive deviations from short-term average temperatures. Abnormalities with respect to average temperatures in recent years have stronger effects than abnormalities with respect to temperatures in baseline periods that climatologists use to identify changes in climate. This suggests that the media are less influenced by scientific accounts of climatic changes than by shorter-term changes in weather patterns.